Web-Based Applications in Healthcare and Biomedicine - Lazakidou, Athina. (Annals of Information Systems,, 2010)
This proposed Special Issue in AoIS will present studies from leading researchers and practitioners focusing on current challenges, directions, trends, and opportunities associated with healthcare organizations and their strategic use of Web-enabled technologies. Healthcare and biomedical organizations are undergoing major transformations to meet the demand for improved access and quality of service, and modern information technologies are helping to process and manage the growing wealth of data involved. Web-based applications offer a sharp increase in data access and management, and they are at the forefront of the broad field of medical informatics. Topics to be covered will include semantic web applications; workflow and process management; content management and portal technology; data and web mining, warehousing, and information collection, curation, and analysis; web-based learning environments; access control and security; transaction management; and tools for implementation.